THE COMPERATIVE ANALYSIS OF CONSUMER BUYING DECISION OF ALL NEW JAZZ AND ALL NEW YARIS CARS (CASE STUDY: CAR OWNER IN MANADO CITY) - Monangin, Phamella Patrycia (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT This study aims to find out the significance influence between Culture, Social, Personal, and Psychological on Customer Buying Decision of All New Jazz and All New Yaris in Manado city. The method of this research is purposive analysis and the data is obtained from questionnaire that distribute to the consumer All New Jazz and All New Yaris. The analysis method Independent Sample T-Test All New Jazz and All New Yaris in Manado. Based on the research that has been conducted, the result showed that Culture, Social, Personal, and Psychological. There’s no significant differences in Customer Buying Decision based on Culture Factor and Social Factor between All New Jazz and All New Yaris in Manado city. However, there’s significant differences in Customer Buying Decision based on Social and Psychological Factor between All New Jazz and All New Yaris in Manado city. Keywords: Consumer Buying Decision